CORRELATION BETWEEN FAT PERCENTAGE AND HANDGRIP STRENGTH IN CHILDREN PARTICIPATING IN THE LUTA QUE TRANSFORMA PROJECT - Moreira, João Vitor de Souza; Molina, Camille dos Reis; Martins, Matheus Silva; Monteiro, Leonardo Olier de Souza; dos Santos, Marcelo Pereira; e Silva, André Calil; do Nascimento, Guilherme de Jesus; Novaes, Jefferson da Silva; Vianna, Jeferson Macedo; Galdino, Leonardo Hadade; Nogueira, Maria Antônia de Jesus; Pantaleão, Diogo; et al. (Seven Editora, 2025)
Judo is a sport that requires handgrip strength (HGS) for the efficient execution of techniques, and this ability is fundamental for controlling the opponent. The aim of this study was to check the correlation between fat percentage and handgrip strength among participants in the “Luta que Transforma” extension project. Eighteen 4th grade elementary school students took part (9 boys and 9 girls), with an average age of 10.13 years. Height, body mass, %G (using a multi-frequency bioimpedanciometer) and PMF (using manual dynamometry) were assessed. The results showed an average %G of 17.31 ± 11.24, with 50% of the participants classified as “normal”. The average MPF was 17.67 ± 6.69 kgf, which is lower than that reported in the literature for judokas in the same age group. Statistical analysis, using the *Spearman* coefficient, showed a very weak correlation between %G and HGS (r: 0.06; 95% CI: -0.52 to 0.43; p: 0.825), diverging from studies that associate higher %G with lower HGS. It can be concluded that although the majority of participants have adequate %G, their HGS is lower than expected, suggesting the need for specific interventions to improve this capacity. Continuous monitoring of students is essential to promote improvements in sports performance and physical development, as well as ensuring health benefits and quality of life.DOI: https://doi.org/10.56238/sevened2025.026-030